Analysis of ESG Disclosure Practices in Healthcare Sector Companies - Asmara, Sukma Mely; Rahmawati, Isna Putri (AKUMULASI: Indonesian Journal of Applied Accounting and Finance, 2024)
This study aims to describe the disclosure of ESG, environmental, social, and governance dimension practices in healthcare sector companies listed on the Indonesian Stock Exchange from 2021 to 2022. This research used a descriptive study to describe ESG disclosure in healthcare companies. The research objects are 28 healthcare sector companies listed on the Indonesian Stock Exchange from 2021 to 2022. The result shows that the ESG disclosure in Indonesian healthcare sector companies based on the GRI Standard needs to be higher and more informative. In the environmental aspect, the average quantity of ESG disclosure is 38.65%, while the quality of disclosure is 31.94%. In the social aspect, the average amount of ESG disclosure is 43.47%, while the quality of disclosure is 31.10%. In the governance aspect, the average quantity of ESG disclosure is 53.82%, while the quality of disclosure is 37.78%.